Developmental dynamics of lncRNAs across mammalian organs and species - Sarropoulos, Ioannis; Marin, Ray; Cardoso-Moreira, Margarida; Kaessmann, Henrik (Nature, 2019)
A transcriptome dataset from seven organs and seven mammalian species throughout development is used to analyse the expression of long noncoding RNAs in tissues within and between species, and at different stages of organ development.
Gesehen am 21.02.2020
Received: 21 October 2018